Draft genome sequence of Lactobacillus plantarum MPL16, a wakame-utilizing immunobiotic strain isolated from swine feces - Villena, Julio Cesar (2017)
The genome of the immunomodulatory Lactobacillus plantarum MPL16, a strain able to ferment wakame (Undaria pinnatifida), is described here. The reads were assembled into contigs with a total size 3,278,495 bp. The genome information will be useful for further specific genetic studies of this strain that evaluate its immunomodulatory and biotechnological properties.